2019
DOI: 10.1001/jamaophthalmol.2019.2513
|View full text |Cite
|
Sign up to set email alerts
|

Motor Vehicle–Associated Traumatic Ocular Injuries Secondary to External Rear-Facing Sideview Mirrors

Abstract: IMPORTANCE Rear-facing sideview mirrors are a potentially reducible source of ocular morbidity following motor vehicle crashes.OBJECTIVE To report cases highlighting shattered glass from sideview mirrors as a potential cause of ocular trauma in motor vehicle crashes.DESIGN, SETTING, AND PARTICIPANTS Case series of 3 patients who presented to Grady Memorial Hospital, a level 1 trauma center and tertiary hospital, between May 5, 2017, and July 10, 2017, with ocular trauma as a result of shattered glass from side… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Rear-view side-mirror induced penetrating and non-penetrating ocular injuries have also been documented in the U.S. A recent retrospective review published in 2019 reported 3 cases of similar globe injuries from a single U.S. institution within just a 3-month time period. 9 All three patients suffered from large corneal and/or scleral lacerations accompanied with significant intraocular damage. Another earlier retrospective review reported 41 patients with ocular or periocular injuries due to rear-view side-mirrors including eyelid/brow lacerations, corneal abrasions, corneal/scleral lacerations, and globe contusion.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Rear-view side-mirror induced penetrating and non-penetrating ocular injuries have also been documented in the U.S. A recent retrospective review published in 2019 reported 3 cases of similar globe injuries from a single U.S. institution within just a 3-month time period. 9 All three patients suffered from large corneal and/or scleral lacerations accompanied with significant intraocular damage. Another earlier retrospective review reported 41 patients with ocular or periocular injuries due to rear-view side-mirrors including eyelid/brow lacerations, corneal abrasions, corneal/scleral lacerations, and globe contusion.…”
Section: Discussionmentioning
confidence: 94%
“… 7 Our case, like the previously discussed case reports, are clear incidents of injury due to isolated damage to the rear-view side-mirror without associated damage to the windshields, side windows or interior rearview mirrors. 6 , 7 , 8 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…The severe eye injuries, such as rupture of globes and retinal detachments, that were caused by blast force or shocks. [2][3][4][5][6][7][8] Most common oculus traumas were related to vehicle crashes [9][10][11][12][13] and sport accidents, [14][15][16][17][18] which mainly focused on rupture injuries of globes and retinal. The contusion ocular injuries often lead to the moderate vision impairment, especially for young patients.…”
Section: Evaluating Ciliary Body Damage Induced By Blunt Low Speed Im...mentioning
confidence: 99%